IMPACT OF INSTITUTIONAL QUALITY ON EDUCATIONAL ATTAINMENT: THE CASE OF LOW-INCOME SSA COUNTRIES - Stephen Akpo Ejuvbekpokpo; Roland Ufuoma Ejedegba; Eko- Raphaels. Melvin U. (Seoul Journal of Economics, 2021)
Education produces many social, political and economic outcomes including improved cognitive competences, higher wages, better health and enhanced economic status. Nations ensure the development of their population by the use of educational intervention. Despite the documented empirical correlations of education attained, there have been scanty researches exploring the impact of institutional quality in low-income SSA countries. The problem facing SSA can be ascertained in the area of weak institutions which leads to poor level of educational attainment and low level of life expectancy which have become the focus of the development agenda in the world as a whole and developing countries in general. The objective of this study is to evaluate the relationship between institutional quality and educational attainment in low-income SSA countries from 2005 to 2013. The research used secondary data sourced from World Bank governance indicators, Transparency International and Heritage Foundation. The analysis was divided into panel data using the fixed effects method (FEM) and generalized method of moments (GMM). Both the panel data analysis and the generalized method of moments of institutional quality and educational attainment indicated that most of the countries investigated exhibits mixed performance in institutional quality. The study recommends policies to reduce corruption in all levels of economic activities. In addition, rule of law need to be strengthened and the educational sector should be refined to train manpower in all aspect of human activities in the region especially the low-income countries in SSA countries.
Keywords: Sub Sahara African countries; educational attainment; institutional quality; rule of law; corruption; Panel data; GMM